Oropharyngeal Administration of Colostrum Increases Salivary Secretory IgA Levels in Very Low-Birth-Weight Infants - Glass, Kristen M.; Greecher, Coleen P.; Doheny, Kim K. (American Journal of Perinatology, 2017)
Aim Oropharyngeal administration of colostrum (OAC) has been proposed to provide mother's early milk to very low-birth-weight (VLBW) infants in the first few days of life. The aim of this study was to test the hypothesis that OAC would increase salivary secretory IgA (SsIgA).Patients and Methods Overall, 30 VLBW infants randomized to receive OAC or sterile water had salivary sampling for SsIgA on the day of life (DOL) 2, 7, and 14. The incidence of late-onset sepsis (LOS) and necrotizing enterocolitis (NEC) was determined prospectively. Within and between-group comparisons were made by paired and independent samples t-tests.Results Baseline characteristics were similar between groups. SsIgA was higher in OAC versus the control group (p < 0.05) on DOL 7, but not subsequently on DOL 14. There was no difference in LOS or NEC.Conclusion OAC increased SsIgA at DOL 7. A large, multicenter trial is needed to determine if OAC decreases LOS or NEC in VLBW infants.
Keywords: colostrum; salivary secretory IgA; VLBW infant; infection